Frozen Shoulder - Evaluating the Effectiveness of Physical Therapy against Other Interventions Like Corticosteroid Injections, Non-steroidal Anti-inflammatory Drugs (NSAIDs), and Surgical Options – A Literature Review - Presak, Michał; Jankowska, Marlena; Baran, Karolina; Jańczyk, Natalia; Mędrysa, Karolina; Pokrzepa, Jakub; Blecharz, Gabriela; Szwech, Julia; Winkowska, Alicja; Mielżyńska, Adrianna (Quality in Sport, 2025)
Frozen shoulder (adhesive capsulitis) is a prevalent musculoskeletal condition characterized by pain and progressive restriction of shoulder joint movement, significantly affecting quality of life. This literature review evaluates the comparative efficacy of physical therapy against other therapeutic interventions, including corticosteroid injections, NSAIDs, and surgical options such as manipulation under anesthesia and arthroscopic capsular release. The study highlights the need for individualized treatment strategies and further research to refine clinical guidelines. The management of frozen shoulder (adhesive capsulitis) requires a tailored approach, considering the stage of the condition and patient-specific factors. Physical therapy remains a cornerstone of treatment, particularly in the frozen and thawing stages, and is most effective when combined with other interventions. While corticosteroid injections demonstrate significant short-term benefits in pain relief and functional improvement, their efficacy diminishes over time unless supported by a structured rehabilitation program. NSAIDs are primarily beneficial for managing inflammation and pain in the early stages but do not significantly alter the course of the condition when used in isolation. Surgical interventions such as manipulation under anesthesia (MUA) and arthroscopic capsular release are reserved for cases resistant to conservative management. Though both surgical options yield comparable outcomes, arthroscopic capsular release is increasingly favored due to its precision and reduced risk of complications compared to MUA. Overall, early intervention with a multimodal strategy incorporating corticosteroid injections, targeted physical therapy, and patient education optimizes outcomes. Future research should focus on identifying patient subgroups that benefit most from specific interventions and on standardizing treatment protocols​.